Word Formation that Occurred in Indonesian Language during Covid-19 Pandemic - Irawan, Bambang (Foremost Journal, 2022)
ABSTRACT Nowadays, almost all countries in the world, including Indonesia, are still facing and struggling with COVID-19 pandemic. In Indonesia, the first case was confirmed by the president on March 2nd, 2020. Since then, Indonesia has been fighting against COVID-19 pandemic. This pandemic is affecting all aspects of human life including language. There is an interesting phenomenon dealing with the emergence of new words during COVID-19 pandemic. As the COVID-19 pandemic progresses, the number of â€˜newâ€™ or â€˜re-emergeâ€™ terms will also be increasing. Most of the termsâ€™ meanings are discoverable through news articles published massively on the internet. The terms that are occurring are not only caused by the new virus that needs certain terms for the medical or scientific matters, but it is also because of the â€˜new normalâ€™ that people are being forced into. This research entitled â€œWord Formation that Occur in Indonesian Language during COVID-19 Pandemicâ€ is aimed to find out what types of word formation that occur in Indonesian language during COVID-19 pandemic. This research employed a descriptive analysis method which belongs to qualitative research. This method was chosen because the researchers described the linguistic phenomenon dealing with word formation. The object of this research was the official website https://covid19.go.id/ which is Indonesian official website that provides any information about COVID-19. The data were collected by reading several sections in https://covid19.go.id/. Therefore, the technique used to collect the data were reading and note taking techniques. The researchers used several steps in collecting the data: (1) reading several sections in https://covid19.go.id/ ; (2) identifying words containing word formation process; and (3) collecting the words in the table. After collecting the data, the researchers went to the next step which was analyzing the data. There were several steps that the researchers took in analyzing the data: (1) data collection; (2) data display; (3) drawing and verifying conclusion. The results of this research showed that there are three types of word formations that occurred which are initialism, blending, and borrowing. Keywords: COVID-19, Morphology, Word Formation